High-efficiency magnetophoretic labelling of adoptively-transferred T cells for longitudinal in vivo magnetic particle imaging - Tay, Rong En (2024)
While adoptive cell therapies (ACT) have been successful as therapies for blood cancers, they have limited efficacy in treating solid tumours, where the tumour microenvironment excludes and suppresses adoptively transferred tumour-specific immune cells. A major obstacle to improving cell therapies for solid tumours is a lack of accessible and quantitative imaging modalities capable of tracking the migration and immune functional activity of ACT products for an extended duration in vivo. Methods: A high-efficiency magnetophoretic method was developed for facile magnetic labelling of hard-to-label immune cells, which were then injected into tumour-bearing mice and imaged over two weeks with a compact benchtop Magnetic Particle Imager (MPI) design. Results: Labelling efficiency was improved more than 10-fold over prior studies enabling longer-term tracking for at least two weeks in vivo of the labelled immune cells and their biodistribution relative to the tumour. The new imager showed 5-fold improved throughput enabling much larger density of data (up to 20 mice per experiment). Conclusions: Taken together, our innovations enable the convenient and practical use of MPI to visualise the localisation of ACT products in in vivo preclinical models for longitudinal, non-invasive functional evaluation of therapeutic efficacy.